A turizmus térszerkezeti hatása a határrégiókban - Székely, Andrea (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
The role and importance of cross-border regions is in the focus of scientific research for a long ago. The theory' of spatial interactions of different actors is an issue of different scientific fields. From the practical side, the regional policy of the European Union has a wide set of instruments for these special - often periferic, underdeveloped, or even in capability for being pioneer of development - areas. With long peace years and expansion of touristic flows, tourist regions models appeared in the tourism geography literature. However, only a few models of cross-border tourist regions are known, and surprisingly most of them are based on North American evidence. We summarize these results with special attention to F.uropean experiences and offer new interdisciplinary research area.